2023
DOI: 10.3390/gels9100836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Bicarbonate on Gel, Antioxidant and Water Distribution of Reduced-Phosphate Silver Carp Surimi Batter under Cold Storage

Jing-Chao Fan,
Guang-Hui Liu,
Kai Wang
et al.

Abstract: The changes in storage loss, water distribution status, gel characteristics, thiobarbituric acid reactive substances (TBARSs), total volatile basic nitrogen, and total plate count of cooked reduced-phosphate silver carp surimi batter during cold storage at 4 °C were investigated. The storage loss, content of free water, pH, hardness, TBARSs, total volatile basic nitrogen value, and total plate count of all cooked silver carp surimi batters significantly increased (p < 0.05) with an increase in cold storage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The T2 can reflect the fluidity of water laterally, and a longer T2 means a higher water fluidity [40]. Thus, the result indicated that the water in the pork batter was tightly bound, resulting in reduced water mobility when added resistant starch [41]. Additionally, the initial relaxation time of T 2b from pork batter with resistant starch showed no significant differences (p > 0.05) with the increase in resistant starch and ice water, but the initial relaxation times of T 21 and T 22 significantly decreased (p < 0.05) when the fat replacement ratio was no more than 50%, resulting in the samples of T3 having the shortest initial relaxation times of T 21 and T 22 , and the samples of T2 and T4 showed no significant differences (p > 0.05).…”
Section: Low-filed Nmrmentioning
confidence: 95%
“…The T2 can reflect the fluidity of water laterally, and a longer T2 means a higher water fluidity [40]. Thus, the result indicated that the water in the pork batter was tightly bound, resulting in reduced water mobility when added resistant starch [41]. Additionally, the initial relaxation time of T 2b from pork batter with resistant starch showed no significant differences (p > 0.05) with the increase in resistant starch and ice water, but the initial relaxation times of T 21 and T 22 significantly decreased (p < 0.05) when the fat replacement ratio was no more than 50%, resulting in the samples of T3 having the shortest initial relaxation times of T 21 and T 22 , and the samples of T2 and T4 showed no significant differences (p > 0.05).…”
Section: Low-filed Nmrmentioning
confidence: 95%